Pattern of Complications among Scabies Patients Living in a Rural Community of Bangladesh - Islam, Kamrul; Jahan, Tarana; Yusuf, Md. Abdullah; Kalam, Md. Abul; Zaman, Md. Shah; Nurunnabi, Mohammad; Hossain, Md. Jahangir (Bangladesh Journal of Infectious Diseases, 2025)
Background: Scabies is a highly contagious skin infestation that poses a significant public health burden in resource-limited settings. In rural Bangladesh, factors such as overcrowding, poor hygiene, and delayed treatment contribute to the high prevalence of scabies and its associated complications, including bacterial super-infections and systemic illnesses. Despite its burden, data on the patterns of complications among affected individuals remain scarce. Objective: The purpose of the present study was to assess the pattern, frequency, and types of complications associated with scabies among patients residing in a rural community of Bangladesh. Methodology: This community-based cross-sectional study was conducted from September 2024 to February 2025 in Dhamsona union under Ashulia thana, Savar, Dhaka, and involving 220 number of clinically diagnosed scabies patients. Data were collected using structured questionnaires, physical examinations, and relevant clinical investigations. Complications were categorized as dermatological (e.g., impetigo, cellulitis, abscess), renal (e.g., post-streptococcal glomerulonephritis), and systemic (e.g., fever, lymphadenitis). Descriptive statistics and chi-square tests were used to analyze the association between demographic factors and complication patterns. Results: Out of 220 scabies patients, 134 (60.9%) developed one or more complications. The most common complication was pigmentary change in skin (50%), followed by Eczematous change in skin (28%), Pyogenic infection (12%), Nodule formation (6%) & Urticaria (3%). Children under 15 years and individuals from overcrowded households had significantly higher rates of complications (p < 0.05). Poor personal hygiene and delayed treatment-seeking behavior were major contributing factors. Conclusion: Scabies remains a neglected but significant health issue in rural Bangladesh, frequently leading to serious complications due to secondary bacterial infections and delayed intervention. Early detection, public health education, and accessible treatment are essential to prevent complications and reduce disease burden. This study highlights the need for integrated community-based scabies control programs. Bangladesh Journal of Infectious Diseases, June 2025;12(1):57-61